RELASI DAN EKSISTENSI LAKI-LAKI DAN PEREMPUAN SEBAGAI GAMBAR RUPA ALLAH MENURUT KEJADIAN 1:26-28 - Grecetinovitria Merliana Butar-butar (Institut Agama Kristen Negeri Tarutung, 2018)
Abstract The P Source tells us that God created man in His image and likeness (Gen 1: 26-27), which makes man different from other creations. In understanding the position of men and women, it is necessary to understand the great difference between the ideal picture (perspective) and the factual state. By that difference, this becomes the background of this research, the writer uses method Library Researc method and build a hypothesis